Clinical Journal of Gastroenterology - Nakase, Hiroshi; Masamune, Atsushi; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The journal publishes Case Reports and Clinical Reviews on all aspects of the digestive tract, liver, biliary tract, and pancreas. Critical Case Reports that show originality or have educational implications for diagnosis and treatment are especially encouraged for submission. Systematic and personal reviews of clinical gastroenterology are also welcomed. The journal aims for quick publication of such critical Case Reports and Clinical Reviews.
Keywords: Gastroenterology; Hepatology; Abdominal surgery; Rectum -- Surgery; Surgical oncology; Gastroenterology; Hepatology; Abdominal Surgery; Colorectal Surgery; Surgical Oncology